Organization of the Reindeer Husbandry in Finland - Filppa, Jouni (Rangifer, 2011)
Reindeer husbandry is practised in the northern parts of Finland in a region that comprises almost all of the Province of Lapland and parts of the Province of Oulu and covers a good third of the Finnish surface. It is governed by the herding co-operative system. Each reindeer owner is a member of a herding co-operative, and the member's respective rights and responsibilities are determined on the basis of the number of reindeer owned by him. The 56 reindeer herding co-operatives have defined borders as well as different surfaces and reindeer volumes. All herding co-operatives are members of the Association of Herding Co-operatives